Clinical-functional peculiarities in the course of bronchial asthma in combination with the hypertonic disease - T. A. Zaripova; I. I. Antipova; I. N. Smirnova; I. Yu. Lyapunova (Бюллетень сибирской медицины)
Clinical-functional peculiarities of bronchial asthma combined with the hypertonic disease have been revealed. It has been found that the combined pathology occurs more often in older age and proceeds with more pronounced clinical symptoms. It is characterized by the disturbed lipid exchange, diastolic disfunction, changes in the vegetative regulation of the cardiac activity. These symptoms should be taken into account in the plan of treatment.